Struktur sosial dan tatanan spasial permukiman Desa Adat Penglipuran, Kecamatan Kubu, Kabupaten Bangli, Provinsi Bali - Dharmadiatmika, I Made Agus; Kohdrata, Naniek (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020DO - 10.24843/JAL.2020.v06.i01.p14, 2020)
The research method was carried out using in-depth qualitative descriptive observation method. The results of the research show that Penglipuran Traditional Village is a village that had a very high social system ranging from development, environment, culture to the formation of awig-awig which is formulated together with the community and for the benefit of the community it self. The Penglipuran Indigenous Village community has very strong socio-cultural values, so that the socio-cultural values ??in the community are able to form a very unique spatial pattern of village spaces. The social values ??that make up the spatial pattern of the Penglipuran Traditional Village spaces are inseparable from the influence of elements of the belief system, respect for the older, history, ecotomy, cultural activities, and awig-awig as a binding non-formal legal basis. The pattern of the Penglipuran Traditional Village space was formed due to the strong influence of Hindu values ??which was implemented with the development of space with the concept of sanga mandala. Changing the function of space and increasing new spaces are formed due to the increase in family members and the needs of families or members of the Penglipuran Traditional Village community. The kinship between neighbors with close family values ??in the Penglipuran Traditional Village is manifested in the existence of access within the yard which connects between them. The economic level of the Penglipuran Traditional Village community is influenced by non-agrarian income and the entry of tourism, resulting in a shift in the function of space and building ornaments.